Which Causes of Moral Beliefs Matter?. Issue 5 (December 2015) - O'Neill, Elizabeth
Abstract : I argue that information about the distal causes of moral beliefs, such as evolution, is only relevant for assessing the epistemic status of moral beliefs in cases where we cannot determine whether the proximal processes producing these beliefs are reliable just by examining the properties of these proximal processes. Any investigation into the epistemic status of moral beliefs given their causes should start with a look at proximal causes—not at evolution. I discuss two proximal psychological influences on moral beliefs—disgust and sympathy—to demonstrate the feasibility of drawing epistemic conclusions from an examination of proximal causes alone.